Comparison of the Effects of Propofol-Dexmedetomidine and Thiopental-Dexmedetomidine Combinations on the Success of Classical Laryngeal Mask Airway Insertions, Hemodynamic Responses, and Pharyngolaryngeal Morbidity - Cakirgoz, Mensure; Demirel, Ismail; Kar, Aysun Afife; Alaygut, Ergin; Sarac, Omurhan; Karagoz, Emre; Akan, Mert (Mdpi, 2025)
Background and Objectives: Dexmedetomidine is a potent selective alpha(2) receptor agonist with analgesic and sedative effects. Many reports indicate that compared to fentanyl, the combination of dexmedetomidine with propofol provides comparably acceptable conditions for a laryngeal mask airway (LMA). However, no study has evaluated the effectiveness of combined dexmedetomidine and thiopental in LMA insertions compared to that of combined dexmedetomidine and propofol. This prospective, randomized, double-blind study aimed to compare the effects of dexmedetomidine with thiopental or propofol on LMA insertion conditions, hemodynamic responses, and pharyngolaryngeal morbidity, which in this study was defined as the presence of postoperative sore throat, dysphagia, or visible blood in the airway following a laryngeal mask airway (LMA) insertion. Materials and Methods: A total of 80 premedicated ASA I-II patients aged 18-65 years were randomized to the propofol group (Group P, n = 40) or thiopental group (Group T, n = 40). Anesthesia was induced by infusing 1 mu gkg(-1) dexmedetomidine over 10 min followed by 2.5 mgkg(-1) propofol or 5 mgkg(-1) thiopental. LMA insertion conditions were evaluated on a scale assessing six variables. Systolic arterial pressure (SAP), diastolic arterial pressure (DAP), mean arterial pressure (MAP), heart rate (HR), and bispectral index values were recorded at baseline; 1 min before; and at 1, 2, 3, 4, and 5 min after an LMA insertion. The baseline values for the systolic arterial pressure (SAP), diastolic arterial pressure (DAP), mean arterial pressure (MAP), heart rate (HR), and bispectral index (BIS) values were recorded before dexmedetomidine infusion. Measurements for all patients were then taken 1 min before and at 1, 2, 3, 4, and 5 min after the LMA insertion Results: Demographic data were similar between the groups. In Group P, the time to loss of eyelash reflex and LMA insertion time were significantly shorter, the apnea duration was significantly longer, and the rates of full jaw opening and optimal LMA insertion conditions were significantly higher when compared with those of Group T (p < 0.05). Group P showed a significantly greater percentage decrease in HR compared to that of Group T at 1 min before and 1, 2, and 3 min after the LMA insertion (p < 0.05). Group T had a greater decrease in SAP and MAP at 1 min before insertion, while the SAP decrease was lower in Group T at 3, 4, and 5 min after insertion. The MAP and DAP values after the LMA insertion showed a greater decrease in Group P compared to in Group T (p < 0.05). The incidence of bradycardia was significantly (p < 0.05) higher in Group P than in Group T. There was no significant difference between the groups in terms of the frequency of hypotension, sore throat, presence of blood, or dysphagia at discharge from the recovery unit (p > 0.05). Conclusions: This study showed that the use of dexmedetomidine with thiopental provided comparably acceptable LMA insertion conditions with more stable hemodynamics compared to propofol.
Keywords: dexmedetomidine; propofol; thiopental; laryngeal mask airway